Diffusion bonding of a microduplex stainless steel to Ti-6Al-4V - Orhan, N; Khan, TI; Eroglu, M (Pergamon-Elsevier Science Ltd, 2001)
In this study, a microduplex stainless steel (AVESTA 2205) and Ti-6Al-4V alloy were bonded for the first time. The bonding variables were chosen on the basis of the importance of grain boundary diffusion in alpha -phase of the titanium alloys. The study showed that the formation of Fe-Cr-Ti intermetallics is more important than sigma -phase formation during bonding. (C) 2001 Acta Materialia Inc. Published by Elsevier Science Ltd. All rights reserved.
Keywords: diffusion bonding; microduplex stainless steel; Ti-6Al-4V